ANALISIS SOSIOPRAGMATIK PADA TINDAK TUTUR KOMUNITAS PEMAIN GAME ONLINE DI KOTA SOLO - Andreas Raymonda; Djatmika Djatmika; Edi Subroto (PRASASTI: Journal of Linguistics, 2016)
This paper was aimed to discuss speech act patterns in online gamer community and to uncover the details of specific terms used by that community, especially those found in Solo. Some approaches and theories about sociopragmatics were used for data analysis dealing with the types and functions of speech act as well as the specific terms used by that online gamer community stayed in Solo. By implementing context analysis method, data collected from participation observation technique, unstructured interview, and elicitation, speech act types from that community could be specified based on the frequency of usage. The highest to the lowest usage speech act types were directive, assertive, expressive, commisive, verdictive, and declarative. Noun was found as the most used class of words in specific terms and followed by the emerge of smaller percentage word class of verb, adjective, and adverb. Key words: sosiopragmatics, speech act, specific term, online game community